Evaluation and Purchase of an Analytical Flow Cytometer: Some of the Numerous Factors to Consider. Issue 1 (1st January 2013) - Zucker, Robert M.; Fisher, Nancy C.
Abstract: When purchasing a flow cytometer, the decision of which brand, model, specifications, and accessories may be challenging. The decisions should initially be guided by the specific applications intended for the instrument. However, many other factors need to be considered, which include hardware, software, quality assurance, support, service, and price and recommendations from colleagues. These issues are discussed to help guide the purchasing process. Curr. Protoc. Cytom . 63:1.28.1‐1.28.11. © 2013 by John Wiley & Sons, Inc.